Dynamics of Calcium during In vitro Microspore Embryogenesis and In vivo Microspore Development in Brassica napus and Solanum melongena - Rivas-Sendra, Alba; Calabuig-Serna, Antonio; Seguí-Simarro, Jose M. (Frontiers in Plant Science, 2017)
Calcium is widely known to have a role as a signaling molecule in many different processes, including stress response and activation of the embryogenic program. However, there are no direct clues about calcium levels during microspore embryogenesis, an experimental process that combines a developmental switch towards embryogenesis and the simultaneous application of different stressing factors. In this work, we used FluoForte, a calcium-specific fluorescent vital dye, to track by confocal microscopy the changes in levels and subcellular distribution of calcium in living rapeseed (B. napus) and eggplant (S. melongena) microspores and pollen grains during in vivo development, as well as during the first stages of in vitro-induced microspore embryogenesis in rapeseed. During in vivo development, a clear peak of cytosolic Ca2+ was observed in rapeseed vacuolate microspores and young pollen grains, the stages more suitable for embryogenesis induction. However, the Ca2+ levels observed in eggplant were dramatically lower than in rapeseed. Just after in vitro induction, Ca2+ levels increased specifically in rapeseed embryogenic microspores at levels dramatically higher than during in vivo development. The increase was observed in the cytosol, but predominantly in vacuoles. Non-embryogenic forms such as callus-like and pollen-like structures presented remarkably different calcium patterns. After the heat shock-based inductive treatment, Ca2+ levels progressively decreased in all cases. Together, our results reveal unique calcium dynamics in in vivo rapeseed microspores, as well as in those reprogrammed to in vitro embryogenesis, establishing a link between changes in Ca2+ level and subcellular distribution, and microspore embryogenesis.